TOURISM AND ENVIRONMENTAL QUALITY MANAGEMENT: COMPARATIVE PERSPECTIVES - BABU P. GEORGE (ASEAN Journal on Hospitality and Tourism, 2007)
Tourism and the environment are intricately and inseparably interlinked, with many positive  relationships as well as several irreversible negative impacts. Destinations of higher environmental quality attract tourists and in that process are also transmuted, either positively or negatively. Drawing evidences largely from the Indian context, the present paper analyzes the root causes of tourism related degradation in environmental quality and suggests alternatives that synergizes tourism and environment. Two case studies are presented: one to show how tourism produces inferior environmental quality and the other to suggest a practical means to overcome the apparent contradiction between conservation and development. It is concluded that the paradigm of ecocultural tourism and the praxis of community based ecotourism could provide useful global frameworks with reference to which locally informed quality-tourism initiatives could be formulated and customized.